Application of Discovery Learning Method to Improve Students' Critical, Tactical, and Innovative Thinking Patterns - Budiyono, Sri; Widodo, Sudiyo; Warsito, Ronggo; Guntoro, Muhammad Yogi; Pratomo, Sigit Adhi; Indrayanto, Bayu; Yuwono, Suhud Eko; Faizun, Ahmad (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to describe how the learning process at Widya Dharma Klatten University is based on the discovery learning method. In connection with this statement, this research focuses on 1) Can the application of discovery learning method improve the learning achievement of students/citizen learners at Widya Dharma University Klaten? 2) Can the application of discovery learning method improve the critical, tactical, and innovative thinking patterns of students/citizen learners at Widya Dharma Klaten University? The type of research used is class action research. Classroom action research is an observation of learning activities in the form of actions, which are deliberately raised and occur in the classroom together. As primary data are students, lecturers, The secondary data are documents of Indonesian Language and Literature Education students in the form of score lists, student rosters, and other records that support this research. The data collection techniques used were tests, observations, interviews, and documentation. The analysis technique used is by using descriptive qualitative which includes three streams of activities simultaneously and continuously during and after data collection, namely data reduction, presentation, and conclusion drawing/verification. The results showed that of the nine students examined, all students experienced a 100% increase. However, of the one hundred percent of students there is one who can be said to have not passed (successfully). However, the student's score continued to rise. The conclusion is 88.888% passed, and 11, 111% did not pass (although the gradation increased).